Global Photocurrent Generation in Phototransistors Based on Single‐Walled Carbon Nanotubes toward Highly Sensitive Infrared Detection. Issue 22 (26th August 2019) - Fang, Hehai; Wu, Peisong; Wang, Peng; Zheng, Zhe; Tang, Yicheng; Ho, Johnny C.; Chen, Gang; Wang, Yueming; Shan, Chongxin; Cheng, Xinbin; Zhang, Jin; Hu, Weida
Abstract: Because of their cost‐effective synthesis and appropriate bandgap opening by various mechanisms, single‐walled carbon nanotubes (SWCNTs) exhibit significant promise for highly efficient near‐infrared photodetection. In this work, the first investigation of manipulating the electrode contact and exciton effect is performed on photocurrent generation of SWCNT transistors by separately depositing Cr or Pd as symmetric source/drain electrodes. Two different photoconducting behaviors of the devices, namely localized and global photocurrent generations, are then observed, where these effects are attributed to thermally assisted tunneling at the 1D‐SWCNTs/3D‐metal contact. A phototransistor with global photocurrent generation is demonstrated having a typical photoconductive effect with a responsivity of 2 A W −1 at λ = 785 nm and a fast rise (decay) time of ≈7.35 µs (11.8 µs). However, the corresponding optical response at 2000 nm is still weak due to low incident photon energy and large exciton binding energy. By further spin coating PbS quantum dots onto the SWCNTs channel, the optical response can be greatly enhanced for 2000 nm irradiation. All these results can not only illustrate the photoresponse of SWCNTs but also indicate that photogating plays a crucial role in these devices, providing valuable insights for the performance enhancement. Abstract : Single‐walled carbon nanotubes (SWCNTs) toward highly sensitive infrared detection (up to ≈2000 nm) is investigated. Further spin coating PbS QDs onto the SWCNTs channel enables an enhanced room‐temperature responsivity at 2.0 µm. An insight of SWCNTs films for practical near‐infrared detection is provided.